Identification of Communication Strategies for Population Control in Indonesia: A Systematic Review - Sari, Chycilia Ayu Medya; Utari, Prahastiwi; Satyawan, Ign. Agung (KnE Social Sciences, 2022)
This article aimed to identify the most effective communication strategy to be implemented by the Indonesian Government to restrict population growth. Through the BKKBN, the Indonesian Government aims to improve information access and promote the National Family Planning Program to all segments of society. This effort has resulted in several studies assessing the communication strategy of BKKBN representatives in disseminating the Family Planning Program in several regions. To determine the most effective communication strategy, researchers must study various scientific journals and then synthesize the findings. This paper employed the systematic literature review method to examine five pieces of literature related to the BKKBN representatives’ communication strategies for disseminating the Family Planning Program. The findings revealed that those targeted were generally teenagers; the most commonly used communication strategies were direct counseling and the use of media through well-planned processes; the communication objectives were understanding and changing people’s behavior to create a prosperous family; and the most frequently used media were direct media (face-to-face counseling), indirect media (television, radio, newspapers), and new media (Facebook). Keywords: family planning, population growth, socialization